2023
DOI: 10.1111/cote.12670
|View full text |Cite
|
Sign up to set email alerts
|

Study of the dyeing properties of saffron and ultrafiltrated saffron powders, as colourants for natural and synthetic fibres

Abstract: There is a noticeable growing interest in the use of natural dyes in contemporary textile dyeing, motivated by the requirements imposed, in favour of environmental prosperity. The use of natural dyes reduces significantly both the energy requirements and the environmental impact of the process. In the present work natural and synthetic fibres were dyed with the dyestuff isolated from Crocus sativus L., after aqueous extraction of the dried stigmas of the plant. Additionally, part of the powder was purified by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…These studies identified at least six different crocins in C. sativus tepals and the remarkable amount of kaempferol derivatives of 126 mg g -1 dry weight [ 21 ]. Owing to these metabolites’ presence in saffron tepals, they have been suggested as an alternative or supplementary medicine against some diseases [ 22 ] and effectively applied as natural pigments in natural and synthetic substrates [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…These studies identified at least six different crocins in C. sativus tepals and the remarkable amount of kaempferol derivatives of 126 mg g -1 dry weight [ 21 ]. Owing to these metabolites’ presence in saffron tepals, they have been suggested as an alternative or supplementary medicine against some diseases [ 22 ] and effectively applied as natural pigments in natural and synthetic substrates [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…These studies identi ed at least six different crocins in C. sativus tepals and the remarkable amount of kaempferol derivatives of 126 mg g -1 dry weight [18]. Owing to these metabolites' presence in saffron tepals, they have been suggested as an alternative or supplementary medicine against some diseases [19] and effectively applied as natural pigments in natural and synthetic substrates [20].…”
Section: Introductionmentioning
confidence: 99%